Retraction - Gamarra LF; Amaro E Jr; Caous CA; Sibov TT; Mamani JB; Cárdenas WH (International Journal of Nanomedicine, 2012)
Cárdenas WH, Mamani JB, Sibov TT, Caous CA, Amaro E Jr, Gamarra LF. Particokinetics: computational analysis of the superparamagnetic iron oxide nanoparticles deposition process. Int J Nanomedicine. 2012;7:2699–2712.It was brought to our attention that the Cárdenas et al paper did not cite a key source paper for the mathematics and approach to modeling the particokinetics of nanoparticles: Hinderliter PM, Minard KR, Orr O, et al. ISDD: A computational model of particle sedimentation, diffusion and target cell dosimetry for in vitro toxicity studies. Part Fibre Toxicol. 2010;7:36.In addition to unacceptable similarities in equations, computer implementation, and use of parameters from the above reference, three of the figures appearing in the paper are nearly identical to those published in the abovementioned Hinderliter et al, while others are very similar to those published in Teeguarden JG, Hinderliter PM, Orr G, Thrall BD, Pounds JG. Particokinetics in vitro: dosimetry considerations for in vitro nanoparticle toxicity assessments. Toxicol Sci. 2007;95(2) 300–312. A number of other relevant citations were not included:Bird RB, Stewart WE, Lightfoot EN. Transport Phenomena. 2nd edition. New York: John Wiley and Sons Inc; 2002:97.Socolofsky SA, Jirka GH. Environmental Fluid Mechanics Part I: Mass Transfer and Diffusion Engineering – Lectures. 2nd edition. Karlsruhe-Germany; 2002:23.Probstein RF. Physicochemical Hydrodynamics – An Introduction. 2nd Edition. New York: John Wiley and Sons Inc; 2003:45.Bejan A. Convection Heat Transfer. 3rd edition. New York: John Wiley and Sons Inc; 2004:515.We have no choice but to retract the publication by Cárdenas et al.